Circulating MicroRNAs in Cancer: Potential and Challenge - Cui, Mengying; Wang, Hongdan; Yao, Xiaoxiao; Zhang, Dan; Xie, Yingjun; Cui, Ranji; Zhang, Xuewen (Frontiers in Genetics, 2019)
MicroRNAs (miRNAs) are endogenous non-coding small RNA molecules that can be secreted into the circulation and exist in remarkably stable forms. Like intercellular miRNAs, circulating miRNAs participant in numerous regulation of biological process and expressed aberrantly under abnormal or pathological status. The quality and quantity changes of circulating miRNAs are associated with the initiation and progression of cancer and can be easily detected by basic molecular biology techniques. Consequently, considerable effort has been devoted to identify suitable extracellular miRNAs for noninvasive biomarkers in cancer. However, several chanlleges need to overcome before the practical application. In this review, we discuss several issues of circulating miRNAs: biological function and basic transport carriers; extracellular cell communication process; roles as reliable cancer biomarkers and usage in targeted cancer therapy; challenges for clinical application